The Relationship between Physical Conditions of the House and the Incidence of Tuberculosis - Siregar, Rahmah Juliani; Yusuf, Susi Febriani; Fernaldy, Devrich (International Journal of Public Health Excellence (IJPHE), 2022)
Tuberculosis is an infectious disease caused by the bacteria cobacterium tuberculosis which mostly attacks the lungs. To find out the relationship between the physical condition of the house and the incidence of Tuberculosis in the community in Sorimanaon Village, Angkola Muaratais District. This type of research is a quantitative analytic observational study. Positive people with a total sample of 51 people. The sampling technique is by observation, direct measurement of the physical condition of the house, interviews, and other supporting data such as recording situation reports. The results of bivariate analysis on clean water facilities have a relationship with the incidence of tuberculosis, p value = 0.017, ventilation with p value = 0.016, house floor with p value = 0.002, residential density p = 0.001. There is a significant relationship between the variables of the physical condition of the house with the incidence of Tuberculosis Chi-Square test below 0.5%. Suggestions for this research is the need for counseling about the requirements of a healthy home and clean and healthy living behavior in tuberculosis patients, especially Pintu Padang Health Center, the patient's family to conduct an early examination of Tuberculosis so that the incidence of Tuberculosis can be minimized.